2019
DOI: 10.3390/s19061401
|View full text |Cite
|
Sign up to set email alerts
|

A Capacitive Micromachined Ultrasonic Transducer-Based Resonant Sensor Array for Portable Volatile Organic Compound Detection with Wireless Systems

Abstract: The development of portable volatile organic compound (VOC) sensors is essential for home healthcare and workplace safety because VOCs are environmental pollutants that may critically affect human health. Here, we report a compact and portable sensor platform based on a capacitive micromachined ultrasonic transducer (CMUT) array offering multiplex detection of various VOCs (toluene, acetone, ethanol, and methanol) using a single read-out system. Three CMUT resonant devices were functionalized with three differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Further mass changes are expected during sensing upon interaction of the analytes with the polymer, which ultimately leads to adsorption [17]. Analytes in the gas phase, such as carbon dioxide, sulfur dioxide, volatile organic compounds (VOCs) including acetone, methanol, ethanol, toluene, benzyl methyl ketone (BMK) and DMMP, and water, are viable for sensing based on mass changes of polymer films [4,27,38,39]. These gas-sensitive films comprising polymers such as poly(styrene-co-allyl alcohol), poly(vinylacetate), poly(capralactone), methylated poly(ethylene imine), poly (vinyl pyrrolidine) and poly {methyl [4-(2-hydroxy-4, 6-bistrifluoromethyl) phenyl] propylsiloxane} have been reported for detecting the analytes mentioned above [4,17,34,39,40].…”
Section: Cmut Functionalization With Sensing Materials and Device Sensmentioning
confidence: 99%
See 1 more Smart Citation
“…Further mass changes are expected during sensing upon interaction of the analytes with the polymer, which ultimately leads to adsorption [17]. Analytes in the gas phase, such as carbon dioxide, sulfur dioxide, volatile organic compounds (VOCs) including acetone, methanol, ethanol, toluene, benzyl methyl ketone (BMK) and DMMP, and water, are viable for sensing based on mass changes of polymer films [4,27,38,39]. These gas-sensitive films comprising polymers such as poly(styrene-co-allyl alcohol), poly(vinylacetate), poly(capralactone), methylated poly(ethylene imine), poly (vinyl pyrrolidine) and poly {methyl [4-(2-hydroxy-4, 6-bistrifluoromethyl) phenyl] propylsiloxane} have been reported for detecting the analytes mentioned above [4,17,34,39,40].…”
Section: Cmut Functionalization With Sensing Materials and Device Sensmentioning
confidence: 99%
“…VOCs such as toluene, acetone, ethanol and methanol can be detected using a CMUT-based resonant sensor array using polymers such as poly(styrene-co-allyl alcohol), poly(ethylene oxide) and poly(isobutylene) as gas-sensitive coatings [30,39]. In the case of toluene detection, the CMUT sensors had a mass sensitivity of 0.8 Hz/fg and a chemical sensitivity of 1.5 Hz/ppm.…”
Section: Cmut Functionalization With Sensing Materials and Device Sensmentioning
confidence: 99%
“…The detection and the measurement of gas concentrations can be carried out using several principles. The most common working principles, sensors, and systems used for gas detection are: electrochemical sensors [1,2], systems based on Quartz Crystal Microbalances [3], sensors based on semiconductors [4,5], optical sensors [6], capacitive sensors [7], cantilever-based sensors [8], and colorimetric devices [9].…”
Section: Introductionmentioning
confidence: 99%
“…It is ambitious to propose a gas sensor which is completely novel (especially for the detection of oxygen and carbon dioxide) with sensitivity, resolution, selectivity, and repeatability better than the ones given by the existing technologies (reported in References [1][2][3][4][5][6][7][8][9][10]). All the mentioned sensors (not pretending to be exhaustive) are complementary in terms of pros and cons, and the best solution can be selected among them for each different application.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that an increase in selectivity can be achieved by coating different CMUT elements with different sensing layers [33,37,46]. Some researchers showed a possibility of making wireless, low power, CMUT-based gas sensors with designs including multiple channels for better selectivity [39,47,48,49]. However, sensor functionalization, while resulting in selective molecular interactions with the analyte, can result in very strong binding and irreversible changes to the molecular structure.…”
Section: Introductionmentioning
confidence: 99%